Urgensi Pendidikan Agama Islam Dalam Meningkatkan Kecerdasan Spiritual Siswa Kelas VIII di SMP Alfa Sanah Cisauk - Wanda Alfiah Misbah; Siti Mariyam (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This study aims to explore the urgency of Islamic Religious Education (PAI) in improving the spiritual intelligence of eighth grade students at SMP Alfa Sanah Cisauk. Spiritual intelligence is an essential aspect of students' holistic development, encompassing the ability to understand the meaning and purpose of life, as well as to develop strong moral and ethical values. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, classroom observations, and school document analysis. The subjects of the study included PAI teachers, eighth grade students, and parents. The results of the study indicate that PAI plays a crucial role in enhancing students' spiritual intelligence. The PAI curriculum not only includes religious knowledge but also spiritual practices that encourage self-reflection, the development of positive values such as honesty, empathy, and respect, and the application of these values in daily life. PAI teachers at SMP Alfa Sanah Cisauk also implement interactive and contextual learning approaches, which facilitate students' deep understanding of religious teachings. Moreover, support from parents and a conducive school environment also contribute to the enhancement of students' spiritual intelligence. This study concludes that PAI is vital in shaping students' character and spiritual intelligence and recommends that schools continuously strengthen PAI programs by involving various stakeholders to achieve optimal results.